Clinical observation of Kaposi sarcoma associated with HIV in a patient with disseminated pulmonary tuberculosis, viral hepatitis B and C - N. V. Nelidova; N. V. Kuzmina; Yu. E. Rusak; E. N. Efanova (Лечащий Врач, 2021)
The article describes the clinical observation of Kaposi sarcoma associated with HIV in a patient with disseminated pulmonary tuberculosis, viral hepatitis B and C. Kaposi sarcoma is a multifocal systemic tumor of endothelial origin with characteristic pathohistological signs associated with the human herpes virus type 8 (HHV-8). There are 4 clinical variants of Kaposi sarcoma: classical, endemic, epidemic, AIDS-associated, and immunosuppressive. The Kaposi sarcoma variant in HIV infection is characterized by rapid progression of the pathological process and multifocal dissemination. Clinical observation. Patient S., 41 years old, was admitted to the Surgut clinical tuberculosis dispensary with complaints of rashes on the skin of the entire body. The first elements of the rash appeared about two months ago. Objectively: the pathological skin process was widespread. Numerous bluish-red spots from 2 to 5 cm in diameter with a smooth surface, lenticular and numular papules, nodes up to 3 cm in diameter of a reddish-brown color with a purple hue, dense elastic consistency were diffusely localized on the skin of the face, trunk, and limbs. The diagnosis of Kaposi sarcoma associated with HIV was made based on clinical and anamnestic data and the results of additional research methods. Specific anti-tuberculosis and antiviral therapies were used in the treatment. Despite the treatment, the patient died as a result of decompensation of the main process. The described observation illustrates the complexity of managing patients with combined infectious pathology. Taking into account immunosuppression, disseminated pulmonary tuberculosis, the appointment of systemic cytotoxic therapy is difficult due to the risk of progression of Mycobacterium infection. The complexity of managing patients with Kaposi's epidemic sarcoma is also due to the high probability of multi-organ lesions and the high potential for dissemination of the process.